Action Competence for Environmental Sustainability : A study of Junior High School Students in Public and Private Schools in Batu City, Indonesia - Silvia, S.; Rahardjanto, Abdulkadir; Husamah, H. (Universitas Pendidikan Mandalika, 2025)
This study aims to describe Â the level, differences between public and private schools, gender differences, the influence of fathers' and mothers' education on action competence for environmental sustainability in junior high school students in Batu City. This study uses a quantitative approach with a descriptive analysis research type. The population in the study was 4,036 junior high school students spread across public and private schools in Batu City. To determine the number of samples using the Slovin formula, so that the number of samples obtained was 1,291 students. Data collection was carried out using an instrument in the form of a questionnaire in the form of a Google form. Respondent characteristic data were analyzed using frequency and percentage. Comparison of two groups of students, namely school status and gender, was analyzed using the Mann-Whitney Test, while comparisons of more than two groups, namely father's and mother's education, were analyzed using the Kruskal-Wallis Test. The results of the study showed that; (1) The level of competency in actions for environmental sustainability in junior high school students in Batu City is in the good category with a high average score, (2) between public and private schools there is a difference in action competence for environmental sustainability in junior high school students in Batu City, (3) there is no difference in gender of students in action competence for environmental sustainability in junior high school students in Batu City, and (4) there is no difference in education of fathers and mothers in action competence for environmental sustainability in junior high school students in Batu City.